Humanistic disciplines and training for work at Escola Técnica Federal do Rio Grande do Norte (1968-1985) (Research, Society and Development, 2020)
Training for work at the Escola Técnica Federal do Rio Grande Norte (ETFRN) during the Military Dictatorship, was immersed in proposals for educational reforms that followed the technicist model and, therefore, emphasized technical knowledge at the expense of humanistic disciplines. This work proposes to analyze the place of human subjects in the training of ETFRN students between 1968 and 1985. We use documentary sources such as school records, class diaries and current educational legislation. We also use oral and bibliographic sources, theses, dissertations and monographs, books and articles. The content analysis, defined by Júlio Aróstegui, served as a basis for understanding the documents and interviews. On oral history, we spoke with Alessandro Portelli and Jose Carlos Sebe Bom Meihy. Notably the Dictatorship has dealt a heavy blow to the humanities in general, and especially to education for work, relegating them to a subordinate place. However, we realized that in addition to the curriculum there was a diversity of approach and meanings that students and teachers could give in everyday life. The voices are dissonant and this shows us that reality is not univocal, hence the importance of bringing to light debates like this, which is still incipient in the History of Professional Education.